Internet-based cognitive behavioral therapy in children and adolescents with obsessive-compulsive disorder: A randomized controlled trial - Hollmann, Karsten; Hohnecker, Carolin S.; Haigis, Anna; Alt, Annika K.; Kühnhausen, Jan; Pascher, Anja; Wörz, Ursula; App, Rehan; Lautenbacher, Heinrich; Renner, Tobias J.; Conzelmann, Annette (Frontiers in Psychiatry, 2022)
Objectives Obsessive-compulsive disorder (OCD) in childhood and adolescence often leads to significant impairment in various areas of life and has a high risk of becoming chronic. Cognitive behavioral therapy (CBT) is the recommended first-line treatment, but it is too rarely implemented in accordance with guidelines and is often not available close to the patient’s home. Importantly, internet-based CBT could help to reduce this gap in care. Having previously successfully demonstrated the feasibility of an internet-based CBT approach, we aimed to assess its effectiveness in a waiting list controlled randomized trial. Methods Children and adolescents aged 6–18 years with a principal diagnosis of OCD received 14 sessions of therapist-delivered CBT via videoconference distributed over 16 weeks. After inclusion, participants were randomly assigned to either the treatment or waiting list group. Participants in the treatment group began treatment immediately after baseline diagnostics, and participants in the waiting list group began treatment after a 16-week waiting period. The primary outcome was a pre-post comparison of OCD symptoms as measured with the Children’s Yale-Brown Obsessive Compulsive Scale (CY-BOCS). Follow-up assessments were conducted for all measures 16 and 32 weeks after completion of treatment. Results A total of 60 children and adolescents were included into the analyses. Over the course of the treatment, CY-BOCS values significantly decreased in the treatment group compared to the waiting-list control group. Cohen’s d between groups was 1.63. After the patients in the waiting-list group also received the treatment, the OCD symptoms decreased significantly in this group as well. This improvement of symptoms increased over the course of the follow-up assessments. Remission rate peaked at the 32-week follow-up, with 68% in the treatment group and 79% in the waiting list group. Importantly, patient satisfaction with treatment was high to very high. Conclusions In our study, OCD symptoms decreased significantly and remission rate was high after internet-based CBT. Those effects were comparable to those found in studies of face-to-face treatment. Although further evidence is needed, these are early indications that our approach may be a viable way to provide access to adequate treatment for children and adolescents affected by OCD.